Surface morphology investigation during in-situ CdS nanoparticles growth in hybrid P3HT:SA films via gas exposure technique - Malik, Syed A.; Naning @ Zin, Fatin Hana (Sumy State University, 2022)
The unique physical features of group II-VI inorganic semiconductor nanoparticles, including their high surface area and nanoscale size, have attracted significant study interest. When these nanoparticles are integrated with organic semiconductor materials, they form multifunctional materials with advantageous features for usage in electronic devices. This study prepared organic/inorganic thin films by depositing P3HT, stearic acid (SA), and Cd2+ ions onto silicon substrates by a novel Angle Lifting Deposition (ALD) technique. The films were then exposed to H2S gas for 2, 4, 6, and 15 h to nucleate CdS nanoparticles within the P3HT:SA matrices. Field Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X-ray (EDX) were used to characterize the hybrid organic/inorganic thin films. Both morphological and elemental studies demonstrated the existence of CdS nanoparticles. The optimized gas exposure time for hybrid polymer P3HT:SA:CdS was 6 h. This study implies that ALD and gas exposure techniques are practical for fabricating hybrid organic/inorganic nanocomposite thin films at room temperature.